The Revolting Child in Horror Cinema - Scahill, Andrew. author. aut Link
IX, 193 p.
Keywords: The monstrous child is the allegorical queer child in various formations of horror cinema: the child with a secret, the child 'possessed' by Otherness, the changeling child, the terrible gang. This book explores the possibilities of 'not growing up' as a model for a queer praxis that confronts the notion of heternormative maturity.